Dampak Perubahan Sosial Budaya Bagi Pendidikan Masyarakat di Lingkungan Pantai Indah Madasari - Nurhidayat Dayat; Miftah Nurul Maarif; Imas Patmawati; Cici Rasmanah; Irpan Ilmi (J-STAF : Siddiq, Tabligh, Amanah, Fathonah, 2023)
The changed of social and cultural is a process that exists in social life and this will continue to change along with the development of science and technology. Since the past, of course, there have been many social or cultural activities in society that have changed, this is none other than the behavior of the people themselves. The purpose of this research is to find out how the impact that occurs from social and cultural changes that occur in society, especially the area of Pantai Indah Madasari. This study uses a qualitative approach with descriptive methods, based on theoretical studies and direct observation. The results of the study found that the impact of socio-cultural changes on education in the Madasari Beach area varied, there were positive and negative impacts. This depends on how society as social and cultural actors use it as a change into something positive or negative.